1983
DOI: 10.1111/j.1545-5300.1983.00229.x
|View full text |Cite
|
Sign up to set email alerts
|

The Limits of Reciprocity in Behavioral Marriage Therapy

Abstract: This reexamination of the values underlying Behavioral Marriage Therapy (BMT) focuses on the central theoretical concept of reciprocity. It is suggested that BMT's emphasis on individuality and instrumental exchange may not be suitable for all couples. An alternative perspective, emphasizing a developmental progression in marriage reciprocity defined by mutual understanding, is seen to be more sensitive to the differing value systems of couples in therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
1987
1987

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Karen and Rick were trained to deal with relapse as only a situational event. Finally, it was postulated that an imbalance would be created within the relationship as Rick assumed a “helper” role (6); therefore, an opportunity was devised for Karen to provide specific reciprocal assistance to Rick (e.g., improving his office filing system) to help return a sense of equity to the relationship.…”
Section: Methodsmentioning
confidence: 99%
“…Karen and Rick were trained to deal with relapse as only a situational event. Finally, it was postulated that an imbalance would be created within the relationship as Rick assumed a “helper” role (6); therefore, an opportunity was devised for Karen to provide specific reciprocal assistance to Rick (e.g., improving his office filing system) to help return a sense of equity to the relationship.…”
Section: Methodsmentioning
confidence: 99%
“…Jacobson (1983) discussed the politics of marital therapy using BMT as an example of his analysis. The political (critical) statements within BMT included a focus on dyads rather than individuals (see Bennun, 1984); an over-emphasis on behavioural and reciprocal change (see Leadbeater and Farber, 1983); and an insensitivity to sex role issues (see Baucom and Aiken, 1984;Margolin et al, 1984). In concluding the discussion Jacobson (1983) suggested that BMT should pay greater attention to the well being of both the individual in the course of treatment as well as the dyad and moderate its exclusive emphasis on behaviour change by exploring cognitive and perceptual processes.…”
Section: Introductionmentioning
confidence: 99%